Historical Dictionary of British Cinema - Burton, Alan; Chibnall, Steve (Rowman & Littlefield Publishers, 2013)
British cinema has been around from the very birth of motion pictures, from black-and-white to color, from talkies to sound, and now 3D, it has been making a major contribution to world cinema. Many of its actors and directors have stayed at home but others ventured abroad, like Charlie Chaplin and Alfred Hitchcock. Today it is still going strong, the only real competition to Hollywood, turning out films which appeal not only to Brits, just think of Bridget Jones, while busily adding to franchises like James Bond and Harry Potter. So this Historical Dictionary of British Cinema has a lot of ground to cover. This it does with over 300 dictionary entries informing us about significant actors, producers and directors, outstanding films and serials, organizations and studios, different films genres from comedy to horror, and memorable films, among other things. Two appendixes provide lists of award-winners. Meanwhile, the chronology covers over a century of history. These parts provide the details, countless details, while the introduction offers the big story. And the extensive bibliography points toward other sources of information.